pengaruh pendaptan asli daerah, dana alokasi umum dan dana bagi hasil terhadap pertumbuhan ekonomi di provinsi aceh - AR, rahmah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
ABSTRACT This study aims to examine the influence of local income, general allocation fund, and revenue sharing fund on Economic Growth in Aceh province. The data used in this research is secondary data. Census method and time series are used with a population of 23 districts/cities in Aceh province during the observation period 2011- 2014. Data analysis used is multiple linear analysis and hypothesis testing uses the coefficient of determination (adjusted R2),partial significance test (t), and significant simultaneous test (F).This study uses the independent variables: local income, general allocation fund, and revenue sharing fund, and the dependent variable: Economic Growth. The results showed that (1) the local income, general allocation fund, and revenue sharing fund simultaneously affect economic growth, and (2) local income, general allocation fund, and revenue sharing fund partially affect economic growth in the province.Keywords: Economic Growth, local income, General Allocation Fund, and revenue sharing fund